Brief Report: HIV Prevention by Australian Gay and Bisexual Men With Casual Partners. (15th December 2015) - Holt, Martin; Lea, Toby; Mao, Limin; Zablotska, Iryna; Prestage, Garrett; de Wit, John
Abstract : Abstract: We analyzed the HIV risk reduction strategies (RRS) used by Australian gay and bisexual men with casual partners. Among 1346 men who reported any condomless anal intercourse with casual partners, 75% frequently practiced at least one RRS. The most common RRS was serosorting, frequently practiced by 55% of HIV-positive and 47% of HIV-negative participants. Condoms were frequently (but inconsistently) used by 17% of HIV-positive, 41% of HIV-negative, and 30% of untested participants. Relying on an undetectable viral load was frequently practiced by 58% of HIV-positive participants. Strategic positioning, withdrawal, and non-HIV-positive men taking antiretroviral medication were less common strategies.